Study on decomposition of primary carbonitrides in H13 steel under high temperature - SUN Xiao-lin; WANG Fei; CHEN Xi-chun; MAO Ming-tao; GUO Han-jie (工程科学学报, 2017)
Optical microscopy (OM), scanning electron microscopy (SEM), and electron microprobe analysis (EMPA) were used to determine the nature of carbonitrides decomposition in H13 hot work die steel under high temperature, including its morphology, size and composition. Most of the original carbonitrides are long strip (Vx,Mo1-x)(Cy,N1-y) ranging between 10~30 μm with a few square (Tix,V1-x)(Cy,N1-y). The result shows that the edge of the carbonitrides becomes saw-toothed after holding at 1200℃ for 2.5 h, and fine decomposed particles are formed. The average length of carbonitrides, mainly (Tix,V1-x)(Cy,N1-y), is reduced to 12.9 μm as increasing the holding time for 10 h. When the steel is held at 1250℃ for 5 h, about 87% of the carbonitrides disintegrate, especially (Vx,Mo1-x)(Cy,N1-y) dissolving and disappearing, and the carbonitrides size is less than 20 μm. When holding at 1250℃ for 10 h, all the carbonitrides remained are (Tix,V1-x)(Cy,N1-y), of which 70% are square and 93% decompose to fine particles, and can be controlled to size below 10 μm. It is deduced that (Tix,V1-x)(Cy,N1-y) decomposition is related to Fe diffusion by EMPA analysis and that the Fe content in (Tix,V1-x)(Cy,N1-y) gradually enhances while Ti and V contents decline. The carbonitrides reliably decompose at the position of small curvature radius and defect position, forming fine particles of 0.1~1 μm. The original carbonitrides disappear by zone dissolution from outer to inner. The equilibrium temperature of carbonitrides dissolution has a relationship with its constituents based on the two-sublattice model, and dissolution temperature for most (Tix,V1-x)(Cy,N1-y) in sample is between 1200℃ and 1246℃, which fits well with the experimental results.